Exploring the influence of e-WOM and destination image on tourist satisfaction and decision-making for revisit intention to Gili tourism in the post-pandemic ERA - Bahari, Astrid Octavia; Irawan, Bambang; Sudaryanto, Sudaryanto; Handriyono, Handriyono (Edelweiss Applied Science and Technology, 2025)
This study investigates the influence of destination image and electronic Word of Mouth (e-WOM) on tourists’ revisit intentions, emphasizing the mediating role of tourist satisfaction. Understanding the factors that shape revisit behavior is essential for sustainable tourism development. The research employed a quantitative approach, collecting data from 124 tourists who had visited the Gili Islands and were active social media users. Data were gathered through online questionnaires and supported by structured interviews to validate respondents’ comprehension of the research variables. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) was utilized to examine the proposed relationships. The results indicate that both destination image and e-WOM have a significant positive effect on revisit intentions. Moreover, tourist satisfaction serves as a critical mediator, strengthening the relationship between destination image, e-WOM, and revisit intentions. These findings suggest that fostering a strong, positive image of the destination and encouraging favorable e-WOM can enhance tourist satisfaction and ultimately increase the likelihood of repeat visits. The study offers practical implications for destination managers to leverage digital platforms and manage online narratives effectively to build tourist loyalty and ensure long-term competitiveness.